Study of thermoanalytical behavior of heavier lanthanides terephthalates in air atmosphere - Costa, B. A.; Nunes, W. D.G. [UNESP]; Bembo, L. H.; Siqueira, A. B.; Caires, F. [UNESP]; Leles, M. I.G.; Ionashiro, E. Y. (Springer Nature, 2018)
Coordination compounds of heavier lanthanides with terephthalate ligand have been synthesized and characterized employing simultaneous thermogravimetry and differential scanning calorimetry (TG-DSC), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR), TG coupled to FTIR, elemental analysis and complexometry. The results from complexometry with EDTA and from TG curves allowed to establish the stoichiometry of these compounds, which are in agreement with the Ln2(TFTa)3·nH2O general formula where Ln represents trivalent lanthanides or yttrium, TFTA is terephthalate and n = 4 (Er, and Y); 4.5 (Tb, Dy, Ho and Tm); 5 (Yb) and 6.5 (Lu). The thermal decomposition of the anhydrous compounds occurs in two or three consecutive and/or overlapping steps, with the formation of the respective oxides: Tb4O7 and Ln2O3 (Ln = Dy to Lu and Y). The TG-FTIR of the evolved gases obtained from the thermal decomposition of the synthesized compounds, identified the formation of CO2 and water as main gaseous products. The FTIR results also led to information about the type of coordination of the isolated compounds which suggest that the lanthanides are linked to the carboxylate groups by a bridging bond.
Keywords: Heavier lanthanides; Lanthanides coordination compounds; Terephthalate; Thermal behavior